“Green Pack” in Function of Green Marketing as a Form of Social Responsibility in Serbia - Raletić, Saša; Beljanski, Dragana (Journal of Economic Development, Environment and People, 2013)
Green marketing is defined as a partnership of all interested stakeholders to sustainable development. This form of marketing is a relatively new form of social responsibility in Serbia and as such it is subject of this paper. The necessity of integration of green marketing in a social responsible behavior is justified by the fact that purely commercial marketing business ignores the possible conflict between short-term desires and long-term benefits of market entities and society, with regard to global environmental problems. The laws are the lower limits of business and the community social responsibility, which includes green marketing, a higher level. Whereas the National Assembly of the Republic of Serbia in May 2009 adopted 16 laws on environmental protection, that is called the “Green Package”. Laws were passed with the aim of regulating the business and social responsibility and green marketing and development. The aim of this analysis is the “Green Package” as a basis for application of green marketing in Serbia. The work will result in efficiencies that are realized by applying the law of “green package” and point to existing gaps.